Effectiveness of custom-made foot orthoses in patients with rheumatoid arthritis: a randomized controlled trial - Reina-Bueno, María; Vázquez-Bautista, María Del Carmen; Pérez-García, Sergio; Rosende-Bautista, Carolina; Sáez-Díaz, Antonia; Munuera-Martínez, Pedro V (Clinical rehabilitation, 2019)
To determine the effect of custom-made foot orthoses versus placebo insoles on pain, disability, foot functionality, and quality of life. Double-blinded randomized controlled trial. University Podiatric Clinical Area. Patients with rheumatoid arthritis. Patients were randomly assigned to either group A, which received custom-made foot orthoses, or group B, which received placebo, flat cushioning insoles, for three months. The primary outcome was foot pain, measured by visual analog scale. Foot functionality, foot-related disability, and quality of life were measured using the Foot Function Index, the Manchester Foot Pain and Disability Index, and 12-Item Short Form Health Survey (SF-12) questionnaires, respectively, at the beginning and at days 30, 60, and 90. A total of 53 patients, aged 59.21 ± 11.38 years, received either the custom-made foot orthoses ( N = 28) or the placebo ( N = 25). For the analysis of the data, only participants who had been measured at the four time points (0, 30, 60, and 90 days) were included. In group A, all variables showed statistically significant differences when comparing the initial and final measurements. Pain showed 6.61 ± 2.33 and 4.11 ± 2.66 in group A, at baseline and at 90 days, respectively, and Group B showed 6.16 ± 1.77 and 5.60 ± 2.71 at baseline and at 90 days, respectively. This was the only variable that showed statistically significant difference between groups ( P = 0.048). The custom-made foot orthoses significantly reduced the participants' foot pain, although they did not have positive effects on disability, foot functionality, and quality of life compared with only cushioning.